2007
DOI: 10.1021/jp065497z
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Investigation of Deactivation of Ru/Al2O3 Catalyst for Preferential CO Oxidation in the Presence of NH3

Abstract: The preferential CO oxidation (PROX) on a Ru/Al2O3 catalyst was investigated at 115−185 °C in the presence of 21−75 ppm NH3. With an increase in [O2]/[CO] ratios, the CO conversion decreased, though it increased in the absence of NH3. In the presence of NH3, the catalytic activity was high at high temperature, which indicates that O2 was consumed over the upstream of the catalyst bed and that the reaction atmosphere in most portions of catalyst bed was reductive. Thus, a reduction atmosphere kept the catalyst … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“… 34 , 35 This results in the reformate containing NH 3 (usually 10–80 ppm) that deactivates the catalyst. 32 , 33 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… 34 , 35 This results in the reformate containing NH 3 (usually 10–80 ppm) that deactivates the catalyst. 32 , 33 …”
Section: Introductionmentioning
confidence: 99%
“…34,35 This results in the reformate containing NH 3 (usually 10−80 ppm) that deactivates the catalyst. 32,33 Previously, we studied the activities of two Ru-based PROX catalysts, the conventional Ru-based PROX catalyst Ru/α-Al 2 O 3 and a Pt−Ru bimetallic catalyst (Pt/Ru/α-Al 2 O 3 ), in the presence of NH 3 . 31 In the deactivated Ru/α-Al 2 O 3 catalyst, we found that the Ru was partially oxidized.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical feedstocks are often contaminated with minor quantities of undesirable compounds such as ammonia or sulfur-containing compounds, and these trace compounds can compete with the primary reactant for active sites, thereby reducing catalyst activity. In some cases these trace compounds can also desorb under changing process conditions (temperature or partial pressures) making the activity loss reversible. …”
Section: Introductionmentioning
confidence: 99%